A NONSTRATIFIED MODEL FOR NATURAL FRACTAL CURVES - Rice-Snow S.; Emert J.W. (My University, 2002)
The stratified structure of Koch curves limits their value as models of nonstratified curves typical in nature, which may nevertheless have statistically self-similar character. Richardson plots for basic and randomized Koch curves are marked by strong, scale-periodic disruptions, and compare poorly with the smoothly sloping, compact Richardson plots derived for some natural, irregular curves. These disruptions relate to the heirarchies of dominant element sizes created in the discrete steps of Koch curve construction, with element vertices acting as attractors for divider steps. We have developed a curve-generation algorithm that adds individual bend elements to a line segment in a nonstratified manner, explicitly following the self-similar limit relation of curve length (L) to added line segment length (r). Values that may be specified include curve fractal dimension (D) and bend element shape (angle of inclination for the added segments). The procedure allows combinations of fractal dimension and element shape, which encompass the range of D values encountered for natural fractal curves. The nonstratified construction method provides useful standard curves for testing and norming of geometric analysis methods commonly applied to complex natural features. In a preliminary test of a multisampling divider method algorithm, the resulting Richardson plots consistently diverge from linear form, and are likely to lead to an overapproximation of D value.
Keywords: DIVIDER METHOD; TESTING; NORMING; KOCH CURVES; SELF-SIMILARITY